2011
DOI: 10.1167/iovs.10-70911
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of NADPH Oxidase Restores Vasoreparative Function in Diabetic CD34+Cells

Abstract: The NADPH oxidase system is a promising target for correcting vasoreparative dysfunction in diabetic EPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 55 publications
4
46
0
Order By: Relevance
“…activity, and superoxide levels were higher in diabetic than in nondiabetic CD34 þ cells and ex vivo NADPH oxidase inhibition in diabetic cells restored migratory function in vitro and enhanced their homing to ischemic retinal vasculature in vivo. 41 This work supports the key role of reducing oxidative stress in restoring CD34 þ cell function.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…activity, and superoxide levels were higher in diabetic than in nondiabetic CD34 þ cells and ex vivo NADPH oxidase inhibition in diabetic cells restored migratory function in vitro and enhanced their homing to ischemic retinal vasculature in vivo. 41 This work supports the key role of reducing oxidative stress in restoring CD34 þ cell function.…”
Section: Discussionsupporting
confidence: 75%
“…Diabetic CD34 þ cells demonstrate reduced endothelial nitric oxide synthase (eNOS) expression, decreased nitric oxide (NO) bioavailability, and a diminished migratory response to the chemokine stromal derived growth factor 1 (SDF-1a). 40 We previously showed that CD34 þ cells are exquisitely sensitive to oxidative injury 41 because increasing eNOS expression in diabetic cells by AVE3085 resulted in increased peroxynitrite levels and did not enhance NOmediated functions in vitro and in vivo. This suggests that increasing the generation of NO was not sufficient to correct CD34 þ cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes reduces the level eNOS, resulting in diminished eNOS activity and decreased NO production, which leads to disturbance in EPC mobilization (Jarajapu, Caballero et al 2011). In addition, diabetes increases eNOS uncoupling and NADPH oxidase expression, resulting in increased ROS generation.…”
Section: Er Stress Angiogenic Progenitor Cells and Vascular Repairmentioning
confidence: 99%
“…In the bone marrow, diabetes increases the level of ROS, which leads to decreased hypoxia, thereby disrupting the stem cell niche. Blocking ROS generation by inhibiting NADPH oxidase reduces the signs of diabetic EPC dysfunction (Jarajapu, Caballero et al 2011). Given the close interrelations between ER stress and oxidative stress, we speculate that increased ROS generation by diabetes may, in turn, induce ER stress resulting in cell apoptosis and/or disturbed equilibrium between the self-renewal and differentiation of bone marrow progenitor cells (Figure 4) .…”
Section: Er Stress Angiogenic Progenitor Cells and Vascular Repairmentioning
confidence: 99%
“…Following the exercise phase, CD34 + cells from pre-diabetic patients had a better migratory response to the chemotactic factor SDF-1α. Impaired chemotaxis to SDF-1α was reported in circulating CD34 + cells from patients with type II diabetes and was related to reduced vasculogenic potential [29]. SDF-1α is essential for developmental and postnatal hematopoiesis and is a hypoxia-regulated chemokine that attracts cells to areas of vessel growth and repair [30].…”
Section: The Influence Of Physical Activity On Cd34 + Progenitor Cellsmentioning
confidence: 99%